Pengembangan Masyarakat Melalui Program Urban Farming di Kelurahan Kutisari, Kota Surabaya - Dini Ayu Triwahyuni; Agief Julio Pratama; Tri Budiarto (Politeknik Pembangunan Pertanian Malang, 2024)
The agricultural sector in the city of Surabaya makes a relatively small contribution considering the limited agricultural land due to land conversion in urban areas and population density which is increasing every year. Urban farming can be an alternative solution to achieve food sovereignty amidst the problem of limited land in urban areas. This research aims to describe the internal and external factors that influence the development of urban farming communities in Kutisari Village. This research uses a combined qualitative and quantitative research approach (mix methods). Data collection methods were obtained from observation, interviews, documentation, questionnaires, and literature studies/related literature. The target of the research is the urban farming community. The results of the research show that internal factors at the level of education are in the middle category (SMA) and are included in the middle class of society in Surabaya UMK income. The majority of community members are men with main jobs as private employees in the productive age range of 40-49 years. External factors on access to information and accountability are in the high category with community participation in the medium category. Supporting facilities in the form of public facility land in Kutisari Village also support these activities.